2008
DOI: 10.1111/j.1365-2400.2008.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mechanically reducing northern pike density on the sport fish community of West Long Lake, Nebraska, USA

Abstract: Removal of piscivores may affect population size structure, abundance and growth rates of the remaining fish community. A total of 572 northern pike, Esox lucius L., was removed from 25-ha West Long Lake, Nebraska from 2003 to 2006. The northern pike population was reduced from 36 fish ha )1 and 22 kg ha )1 in 2002 to 20 fish ha )1 and 9 kg ha )1 in 2006. The northern pike population shifted to dominance by smaller individuals. Relative abundance increased for bluegill, Lepomis macrochirus Rafinesque, but rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Pierce et al 1995;Jolley et al 2008;Arlinghaus et al 2010;Pierce 2010). In all statistical models examined, the only or most important factor on pike record size structure was commercial fisher ID, suggesting that the type of commercial fishing had a strong impact on pike size structure.…”
Section: Fishery-related Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Pierce et al 1995;Jolley et al 2008;Arlinghaus et al 2010;Pierce 2010). In all statistical models examined, the only or most important factor on pike record size structure was commercial fisher ID, suggesting that the type of commercial fishing had a strong impact on pike size structure.…”
Section: Fishery-related Factorsmentioning
confidence: 94%
“…It is well known that trophy pike are very vulnerable to even slight fishing pressure and very protective regulations are needed to avoid substantial size truncation on exploited pike stocks (e.g. Pierce et al 1995;Jolley et al 2008;Arlinghaus et al 2010;Pierce 2010).…”
Section: Fishery-related Factorsmentioning
confidence: 99%
“…Conversely, Yellow Perch and White sucker increased in abundance following the removal of Northern Pike from harriet lake, UsA (Colby et al 1987). Bluegill (Lepomis macrochirus) in West long lake, UsA responded positively to a reduction in Northern Pike biomass by approximately 50%, but Yellow Perch did not (Jolley et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Based on gill-net catchability and annual mortality, the relative abundance of Northern Pike (≥537 mm) in Pactola Reservoir was estimated at 3.1 fish/ha (i.e., 996 fish/318 ha). Although lower than that typically reported for shallow, productive lakes (e.g., 20-30 fish/ha: Jolley et al 2008) our density estimate was within the range reported for other studies. In College Lake, Colorado, a 7-year study of Northern Pike (≥550 mm) reported densities ranging from 3.7 to 6.7 fish/ha (Willis et al 1984).…”
Section: Discussionmentioning
confidence: 99%